KESESUAIAN PENGASUHAN (PARENTING FIT) DI PERUSAHAAN MULTI BISNIS: STUDI KASUS KELOMPOK “TRANSPORTASI” - Ningky Munir (Journal of Business Strategy and Execution, 2010)
A multibusiness company usually consists of a parent company or a company act as holding company and one or more subsidiaries or strategic business units. Multibusiness companies create value by influencing – or parenting – the businesses they owned. A good fit between a parent and its businesses will create value, a bad one will destroy it. Based on the framework developed by Goold et al. (1994) a study was conducted to assess the fit between characteristics of the parent and of its businesses in “Transportasi” Group. Parent’s characteristics consists of five groups: the parent’s mental maps; the parenting structures, systems, and processes;  functions, central services, and resources; people and skills; and decentralization contracts. Characteristics of businesses consists of three groups: business definition; parenting opportunities; and critical success factors. A qualitative case study approach from Yin (1994) was used to understand parental value-creation in “Transportasi” Group. From this qualitative research in the case of “Transportasi” Group, we found that there are good fit between the parent and most its businesses. Values were created by the parent through stand-alone influence, linkage influence, and corporate development approaches.  Finally, managerial implications are discussed and brief conclusion is presented.